Analisys of pectoralis major tendon in weightlifting athletes using ultrasonography and elastography - Alberto de Castro Pochini; Mario Ferretti; Eduardo Felipe Kin Ito Kawakami; Artur da Rocha Corrêa Fernandes; Andre Fukunishi Yamada; Gabriela Clemente de Oliveira; Moisés Cohen; Carlos Vicente Andreoli; Benno Ejnisman (Einstein (São Paulo))
ABSTRACT Objective To evaluate tendinopathy of the pectoralis major muscle in weightlifting athletes using ultrasound and elastography. Methods This study included 20 patients, 10 with rupture of the pectoralis major muscle and 10 control patients. We evaluated pectoralis major muscle contralateral tendon with ultrasonographic and elastography examinations. The ultrasonographic examinations were performed using a high-resolution B mode ultrasound device. The elastography evaluation was classified into three patterns: (A), if stiff (more than 50% area with blue staining); (B), if intermediate (more than 50% green); and (C), if softened (more than 50% red). Results Patients’ mean age was 33±5.3 years. The presence of tendinous injury measured by ultrasound had a significant different (p=0.0055), because 80% of cases had tendinous injury versus 10% in the Control Group. No significant differences were seen between groups related with change in elastography (p=0.1409). Conclusion Long-term bodybuilders had ultrasound image with more tendinous injury than those in Control Group. There was no statistical significance regarding change in tendon elasticity compared with Control Group.